Magnitude, Characteristics, Maternal and Feto-Neonatal Outcomes of Obstetric Emergencies in Western Ethiopia, Nekemte, Ethiopia - Woyessa, Ashenafi Habte; Caffo, Jote Markos; Palanichamy, Thanasekaran (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: In Ethiopia very little or probably nothing is known about the significance of obstetric emergencies. This study was therefore aimed at assessing magnitude, characteristics, and outcomes of obstetric emergencies in western Ethiopia. Study Design: Institution based prospective cohort study was employed from January to June 2017. To select the hospitals, area sampling technique was used. Total of 567 pregnant women with obstetric emergencies presented and treated in respective hospitals during the study periods and met the inclusion criteria were consecutively included. Results: Majority (91.7%) of the identified obstetric emergencies have led to termination of pregnancy. Significant proportions of pregnant women (11%) who reached health facility died of obstetric emergencies. Pregnant women with obstetric emergencies traveled to facility carried by people were found to have died about 8 times more likely as compared to those who were transported by ambulance. While 29.21% of women gave birth to normal life births, stillbirth and neonatal death were 8.02% and 7.4% respectively. Higher number of neonatal death was also observed among mothers in whom final mode of delivery was a cesarean section (AOR: 0.19(0.05, 0.62)) compared to spontaneous vaginal delivery. Conclusion: This study has revealed that obstetric emergencies are responsible for the significant number of maternal and perinatal death. If the women have been accessed early and received optimum emergency care, many cases of the occurred death would have been prevented. Better outcome can be achieved through maximum utilization of quality and comprehensive antenatal care and organized pre-hospital obstetric emergency services.